Enhancing the dechlorination of CuCl residue using a microwave sulfation-roasting method: Process optimization and mechanism investigation. Issue 2 (April 2023) - Niu, Yifan; Yang, Yongchao; Le, Thiquynhxuan; Fang, Shuaibing; Gong, Siyu; Tian, Shihong; Ju, Shaohua; Xu, Lei
Abstract: Spent CuCl residue produced from zinc hydrometallurgy is a typical toxic and hazardous solid waste as well as a secondary resource owing to its high contents of chlorine and valuable metals (Pb, Cu, Zn). The removal of chlorine from the CuCl residue and recycling of valuable metals are critical issues for the copper slag resource treatment process. In this study, a novel method of microwave sulfation-roasting under an oxygen atmosphere is used to improve the dechlorination process, and various parameters, such as roasting temperature, duration, sulfuric acid concentration, and liquid/solid ratio, are optimized. First, according to thermodynamic calculations, the addition of H2 SO4 can significantly decrease both the roasting temperature and time needed for microwave oxidation-roasting. The dechlorination experimental results reveal that the dechlorination rate of the CuCl residue is as high as 91.91% under a temperature of 250 °C, holding time of 120 min, sulfuric acid concentration of 70%, and liquid-solid ratio of 1.42. The microstructure, chemical composition, and phase changes of the CuCl residue before and after roasting are characterized using scanning electron microscopy coupled with energy-dispersive spectroscopy, X-ray fluorescence and X-ray diffraction; further, the mass contents of the main elements in the roasting product and tail gas absorption solution are determined by chemical analysis, Evidently, the selective heating property of microwaves produces more holes and cracks in the copper slag, which can provide a new reaction channel for H2 SO4 and CuCl slag reactions, and almost all CuCl in the copper slag is completely removed by transformation into CuO, CuSO4 and Cu2 O(SO4 ). Simultaneously, a large number of gas by-products produced in the dechlorination process, such as SO2 and Cl2, can be absorbed by the NaOH solution. Therefore, no pollution is generated in the environment. These findings illustrate that microwave sulfation-roasting is an effective method for promoting the treatment and recycling of CuCl waste residues. Graphical Abstract: ga1 Highlights: Microwave heating was proposed to realize the chlorine removal from CuCl residue. The thermodynamic analysis demonstrated the viability of dechlorination reaction. Sulfating roasting can reduce roasting temperature and time by half. The dechlorination rate of CuCl residue under optimal conditions is 91.91%. CuCl in residue was completely removed by transforming into CuO and CuSO4 .